A framework for sustainable adaptive reuse: understanding vacancy and underuse in existing urban buildings - Armstrong, Gillian; Wilkinson, Sara; Cilliers, Elizelle Juanee (Frontiers in Sustainable Cities, 2023)
Cities have been built on the benefits of density, proximity and connectivity. However, the recent COVID-19 pandemic, along with continuously evolving communication technologies, has seen an increase in vacancies and underuse of urban buildings, challenging the agglomeration benefits of cities and our understanding of business-as-usual. It is by reflecting on these continuous changes in our urban environment, that we can better understand the dynamics in play, the various user needs, the temporary or permanent nature of these changes, and possible adaptive strategies to navigate our future towards a more sustainable and resilient state. This paper therefore presents a systematic literature review, using PRISMA, to examine and map how vacancy intersects with adaptive reuse literature. The review examined 43 academic articles, and reveals research predominately focuses on whole-building adaptive reuse of completely vacant buildings. The review highlighted that vacancy is mainly assumed in research, and both vacancy and adaptive reuse are insufficiently unpacked. A new adaptive reuse framework is proposed to address the misalignment between realities of how vacancy is distributed in building stocks and the focus on whole building adaptive reuse. The framework is set to inform urban policy development supporting sustainable reuse. This paper presents a point of departure to understand how adaptive planning approaches could be applied to enhance broader sustainability and resilience initiatives.